2013
DOI: 10.1108/13598541311293140
|View full text |Cite
|
Sign up to set email alerts
|

The lean and agile purchasing portfolio model

Abstract: Purpose -The aim of this paper is to present a purchasing portfolio model for determining purchasing strategy at the component level of a product to support business strategy, addressing weaknesses in the often cited Kraljic-type models. The work draws on Fisher's model to match supply strategy to product nature. However, Fisher's model was criticised very recently by Lo and Power in this journal because it is unclear how the "leagile" option should fit into it. This paper addresses this issue. Design/methodol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(73 citation statements)
references
References 58 publications
0
70
0
3
Order By: Relevance
“…Pairwise comparisons generate more information and therefore, improve judgment consistency [48]. Therefore, the sample size of 30 experts/respondents is considered to be satisfactory for this research [48,49]. In line with Saaty's [48] suggestion, the geometric mean approach was preferred over the arithmetic mean to combine the individual pair wise comparison judgments to obtain the consensus pair wise comparison judgment matrices for the entire team.…”
Section: Research Setting and Analysismentioning
confidence: 99%
“…Pairwise comparisons generate more information and therefore, improve judgment consistency [48]. Therefore, the sample size of 30 experts/respondents is considered to be satisfactory for this research [48,49]. In line with Saaty's [48] suggestion, the geometric mean approach was preferred over the arithmetic mean to combine the individual pair wise comparison judgments to obtain the consensus pair wise comparison judgment matrices for the entire team.…”
Section: Research Setting and Analysismentioning
confidence: 99%
“…Belekoukias et al's (2014) findings also went on to demonstrate that certain lean TPRCs were associated with small organisations as opposed to large organisations. Although there are mixed findings concerning firm size and lean production (Negrao et al, 2017), as the literature generally associates lean and agile production with large and small organisations respectively, the following two hypotheses were developed: Mason-Jones et al (2000) suggested that SCs, generally speaking, can either be lean, agile or 'leagile' (Drake et al, 2013), as depicted in Figure 1. The latter (leagile) SC, also referred to as the hybrid SC (Huang et al, 2002), is a combination of both paradigms encompassing a total SC strategy which involves a decoupling point.…”
Section: Firm Sizementioning
confidence: 99%
“…To some extent, their approach addresses one of the weaknesses of portfolio methods, which is their limits in terms of the operationalization of the dimensions and measuring variables. Lee and Drake (2010), and Drake et al (2013) extended Kraljic's purchasing portfolio at the component level of a product to support business strategy. Pagell et al (2010) extended Kraljic's model by expanding the 'profit impact' dimension to 'risk to profits, the environment and/or society'.…”
Section: Literature Reviewmentioning
confidence: 99%